2017
DOI: 10.1136/jech-2017-209166
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and causes of death among homeless in Finland: a 10-year follow-up study

Abstract: Homelessness is associated with a fivefold mortality compared with the controls, and especially homeless aged ≤50 years have an increased risk of death. Being homeless eliminates the protective effects of marriage, employment and education on mortality risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 28 publications
4
14
1
Order By: Relevance
“…Our study confirms previous findings that compared to the general population, homeless people die younger 1 11 and have complex comorbidities and a high symptom burden at the end of life. 19 22 , 24 , 34 37 Although the end of life was recognised for three-quarters of the homeless persons in our study, it was difficult to specifically predict prognoses and identify palliative care needs: whereas some patients revived prodigiously, others deteriorated rapidly once admitted to the shelter-based nursing care setting.…”
Section: Discussionsupporting
confidence: 91%
“…Our study confirms previous findings that compared to the general population, homeless people die younger 1 11 and have complex comorbidities and a high symptom burden at the end of life. 19 22 , 24 , 34 37 Although the end of life was recognised for three-quarters of the homeless persons in our study, it was difficult to specifically predict prognoses and identify palliative care needs: whereas some patients revived prodigiously, others deteriorated rapidly once admitted to the shelter-based nursing care setting.…”
Section: Discussionsupporting
confidence: 91%
“…There is no information relating to the morbidity and mortality amongst the homeless in South Africa. Several studies have shown mortality and morbidity rates to be higher in the homeless [13][14][15]. Homelessness itself is an independent risk factor for mortality for certain conditions, however mortality rates were higher in the homeless in those with substance abuse disorders and infectious diseases [16].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, they face specific challenges and barriers to accessing healthcare, often resulting in high rates of acute care use (Fazel et al, ). Furthermore, homelessness has shown to be an independent risk factor for mortality, with average ages of mortality varying roughly between 50 and 65 years in different studies in Western, high‐income countries (Baggett et al, ; Henwood, Byrne, & Scriber, ; Morrison, ; Nielsen et al, ; Stenius‐Ayoade et al, ). Therefore, at these generally still considered middle ages, homeless people are already classified as old (Fazel et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…A similar demographic trend has been observed in the Netherlands: among homeless people receiving help from Dutch social relief facilities, the proportion of people older than 50 gradually increased, from 19% in 2009 to 26% in 2015 (Federation of Shelters, ). While the excess mortality among younger homeless people mainly results from external causes, such as injury and poisoning, older homeless people mainly die from chronic medical conditions, such as respiratory and cardiovascular diseases (Baggett et al, ; Stenius‐Ayoade et al, ). These findings suggest that differences between older and younger homeless people might also be present for other clinically relevant health outcomes.…”
Section: Introductionmentioning
confidence: 99%